Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 51715 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Cnidaria", { "or" : [ "Geometry POLYGON((175 75,175 50,180 50,180 75,175 75))", "Geometry POLYGON((-180 75,-180 50,-155 50,-155 75,-180 75))" ] }, "HasCoordinate is true" ] } The dataset includes 51715 records from 38 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0093896-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences